The Effect Of The Rally Robin Strategy On Developing The Skill Performance Of Art Education Students In The Mural Art Course (Journal of the College of Basic Education, 2026)
The current research aims to identify the extent of the impact on using the Rally Robin strategy in development.The skill performance of students in the Department of Art Education in the subject of mural art.To achieve the research objective, the researcher formulated the following two null hypotheses:There are no statistically significant differences at the (0005) significance level between the mean ranks of the experimental group and the mean ranks of the control group in the post-test cognitive achievement test in the subject of mural art. 2.There are no statistically significant differences at the (0.05) significance level between the mean ranks of the experimental group and the mean ranks of the control group in the skills performance test in mural art.Dimensionally.The current research population consisted of fourth-year students in the Art Education Department at the College of Basic Education, Al-Mustansiriya University, and Maysan University during the 2025-2026 academic year (morning studies). The total number of students in both departments was 215. The research sample was selected purposively from the Art Education Department at the College of Basic Education, Al-Mustansiriya University, as the field for the research, given that the researcher is an art instructor in the department. The sample comprised fourth-year students studying mural art, distributed across four classrooms. The researcher randomly selected classrooms 2 and 3, totaling 64 students. These students were divided into two groups: an experimental group of 30 students (13 male and 17 female), and a control group.The second control group had (30) students, including (14) male students and (16) female students.The researcher adopted the experimental method as it was the appropriate method to achieve the research objective.The researcher used appropriate data tabulation tools, namely: the cognitive achievement test.The skills test and observation formThe researcher used the following statistical methods with the assistance of the SPSS statistical programIndependent samples t-test, chi-square test for good fit2.Discrimination equation for objective items, difficulty equation for objective items, effectiveness equation.3.Incorrect alternatives for objective items, effect size equation, Lena Square 12.Pearson correlation equation, Querez-Richardson equation 20.The researcher reached a set of results, including:The experimental group that studied mural art using the Rally Robin strategy performed better on the post-test than the pre-test due to the application of the Rally Robin strategy. There were significant differences in favor of the post-test.A set of suggestions, including:Applying the Rally Robin strategy to other variables, such as ceramics.Applying the Rally Robin strategy in design techniques.The researcher recommended several measures, including:Adopting the current study in teaching mural art to fourth-year art education students in colleges of basic education.